algebra

posted by .

solve the following using substitution
8x-4y=16
y=2x-4

8x-4(2x-4)=16
8x-8x+16=16
0x+16=16
so what do i do now?

  • algebra -

    Those two equations are the same.
    Look at your first equation dividing both sides by 4
    2 x - y = 4 or y = 2x-4 which is the second equation exactly. There is no intersection of a line with itself in a point. The system of two equations given has no solution.

  • algebra -

    Thank you that is what I thought but wasn't sure when I did not come up with an answer.

  • algebra -

    uyg

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    how do you solve this system? I'm using substitution.. y=3x+4 y=-x^2 First I combined it: -x^2=3x+4 I don't know how to solve it now..
  2. algebra 1

    how do you solve the following questions using the substitution method?
  3. algebra

    i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
  4. Algebra

    Solve the following system using substitution: y = x + 2 y = 3x I don't understand this question.
  5. algebra

    Solve the following system using the substitution method: 3x + y = -3 y = 2x + 7
  6. algebra

    Solve the following system using the substitution method: 6x - 2y = -4 y = 3x + 2
  7. Algebra

    Solve the following system of equations using the substitution method:5x-7y=-18 and 4x+3y=20
  8. math

    Four years from now Emily will be as old as Cathy is now. Seven years ago, the sum of their ages was 22. Write a system of equations to model this situation and solve it using substitution to determine how old the girls are now.
  9. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.
  10. algebra HELP PLEEEEASE

    Solve the following system using elimination or substitution. show your work. y = x^2 - 2x - 6 y = 4x + 10 Please explain how to do this and the answer! THANKS!

More Similar Questions